MicroRNA-147 suppresses human hepatocellular carcinoma proliferation migration and chemosensitivity by inhibiting HOXC6 - Sui, Cheng-Jun (Am J Cancer Res, 2016)
Patients with hepatocellular carcinoma (HCC) experience poor prognosis and low survival rates. In this study, we explored the molecular mechanism of microRNA-147 (miR-147) in regulating human HCC. We firstly used quantitative RT-PCR (qRT-PCR) to compare the expression levels of miR-147 between 7 HCC and two normal liver cell lines, as well as 10 paired primary HCC tissues and their adjacent non-carcinoma tissues. We found miR-147 was down-regulated in both HCC cell lines and primary HCCs tissues. HCC cell lines HepG2 and HuH7 were transfected with lentiviral vector of miR-147 mimics. We found overexpressing miR-147 significantly inhibited HCC in vitro proliferation and migration, increased 5-FU chemosensitivity, and reduced in vivo tumorigenicity. Luciferase, qRT-PCR and western blot assays showed that HOXC6 was the downstream target of miR-147, and both gene and protein levels of HOXC6 were down-regulated by miR-147 in HCC cells. SiRNA mediated HOXC6 knockdown inhibited in vitro proliferation and migration, and increased 5-FU chemosensitivity in HCC. On the other hand, HOXC6 overexpression reversed the inhibitory effect of miR-147 on HCC in vitro proliferation. Therefore, our results suggest that miR-147 can modulates HCC development through the regulation on HOXC6.